Design and conduct of equivalence trials - Durkalski-Mauldin, Valerie (Henry Stewart Talks, 2007)
Equivalence trial study design, Selection of an acceptable margin of equivalence/non-inferiority, Selection of the control (placebo/active/both), Confidence interval or hypothesis testing, Approach, Analysis population, Trial conduct
Archived at 2018/05/31